Entropic stabilization in lithium-rich transition metal layered oxides – A perspective - Sven Burke; Minghao Zhang; Jason R. Croy; Ying Shirley Meng (Next Materials)
In this paper we offer a new perspective on how the principles of high entropy design for oxide materials can be applied to lithium rich transition metal oxide cathodes. We discuss the structure, unique properties, and synthetic dependence of lithium rich transition metal oxide cathodes as well as some background on high entropy oxides. We then discuss the benefits of entropic stabilization in reducing the rigor and increasing the consistency of synthesizing phase pure cathodes materials. We draw parallels between the established temperature, time and transformation relationships used in synthesis of materials and electrochemistry to propose a voltage, time, and transformation analogue that can be used to help explore the phase transformations of lithium rich transition metal oxide cathodes over cycling. This proposed voltage, time, and transformation system is then used to explore the use of entropic stabilization of lithium rich transition metal oxide cathodes during electrochemical cycling. Finally, considerations for the design and limitations of entropic stabilization for lithium rich transition metal oxide cathodes are discussed, and solutions are offered.